DOES THE ROLE OF RELIGIOUS RITES AND RITUALS DIMINISH ITS SIGNIFICANCE FOR MUSLIM FAMILIES IN THE REPUBLIC OF NORTH MACEDONIA? (Religious dialogue and cooperation, 2021)
According to the percentage of Muslims in the totalpopulation of the country, North Macedonia is on the third place inEurope. With about one third of the entire population being Muslim,our country is right after Albania and Bosnia and Hercegovina.Islam is an Abrahamic monotheistic universal religion and the secondlargest religion in the world. The followers of this religion are calledMuslims. Muslims believe that God gave his divine word in the formof revelations through various prophets and that Muhammad wasthe last of God’s Messengers. Every religion has its own religioustraditions and customs that have existed for centuries.Certain sacred practices and rituals are very important to Muslims.They are a significant way that enables followers of Islam toremember history, express conviction, and grow in devotion.Some rituals are practiced daily, like prayer; others are practicedannually, like those aligned with specific Islamic holidays. The FivePillars of Islam are five practices regarded by all sects of the Islamicreligion as essential to the Muslim faith.Although there are important differences between Christianity andIslam regarding traditions, customs and cultural heritage. However,in both religions, due to the secularism in our country, the impressionis that religion diminishes its meaning in everyday life. Young peopleadapt to the contemporary way of life that brings great changes inthe practice of religious rituals and practices. This paper is aboutreligious rituals and customs as religious elements and their meaningfor Muslim families in Macedonia. The paper aims to determinewhether and how often Islamic rituals and practices are practiced.Specifically, does their practicing reduce the importance for Muslimfamilies? For the purposes of this paper, a quantitative survey of60 Muslim religious subjects’ wаs conducted to answer questionsrelated to their views on religion and its practice.
Keywords: Muslim believers; Islamic religion; Muslim rituals; Muslim families